Optimizing Success in Competing in the International Market in the Context of the Globalization Era - Arif Maulana Oscar; Elsa Safitri Siadari; Hamido Julius; Vania Apriani Pakpahan; Suma Budi Rambe; Feronica Simanjorang (LPPM Institut Studi Islam Sunan Doe, 2024)
The purpose of this research is to find out how to optimize success in the international market in the context of the globalization era. This research is a literature review research in which the data is taken from various reliable sources, both articles, books or other research sources. The results of this study are international organizations playing an important role in facing challenges and taking advantage of the opportunities posed by globalization. For example, the World Trade Organization (WTO) plays a role in formulating international trade rules and facilitating negotiations between its member countries to reduce trade barriers. In addition, regional organizations such as the European Union (EU) and ASEAN also contribute to promoting free trade among their member countries through agreements such as the common market and customs union. Through cooperation and negotiations at the international and regional levels, these organizations seek to create an environment that supports international trade and optimizes the benefits derived from globalization. Although challenges and differences of opinion still exist, international organizations remain a vital platform for optimizing success in international markets in the context of the current era of globalization.